1995
DOI: 10.1111/j.1442-200x.1995.tb03677.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori colonization in children with peptic ulcer disease III. Diagnostic value of the 13C‐urea breath test to detect gastric H. pylori colonization

Abstract: The efficiency of the 13C‐Urea Breath Test (13C‐UBT) for the detection of Helicobacter pylori colonization in gastric mucosa was evaluated. The 13C‐UBT was performed in five pediatric and six adult subjects who had had upper gastrointestinal endoscopy within 2 weeks. H. pylori colonization was confirmed in two pediatric and three adult subjects with peptic ulcer combined with antral gastritis, by histological examination of antral biopsy specimens. When an individual with H. pylori colonization ingested a solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The 13 C‐UBT is ideally suited for the determination of H. pylori status in children, although until very recently there was a paucity of adequate data to validate its routine use. However, several recent studies have confirmed that the UBT has in children the same accuracy as in adults 18–42 . In the other extreme of life, some studies have confirmed, in conditions of real clinical practice that the UBT is also a reliable test of H. pylori diagnosis in elderly patients 43 …”
Section: Introductionmentioning
confidence: 95%
“…The 13 C‐UBT is ideally suited for the determination of H. pylori status in children, although until very recently there was a paucity of adequate data to validate its routine use. However, several recent studies have confirmed that the UBT has in children the same accuracy as in adults 18–42 . In the other extreme of life, some studies have confirmed, in conditions of real clinical practice that the UBT is also a reliable test of H. pylori diagnosis in elderly patients 43 …”
Section: Introductionmentioning
confidence: 95%
“…There have been rapid advances in research on Helicobacter pylori infections since this organism was first successfully isolated and cultured by Warren and Marshall in 1983 1 . The organism, H. pylori , has been shown to play a role in many gastrointestinal disorders, including chronic atrophic gastritis, peptic ulcer disease, gastric mucosa‐associated lymphoid tissue lymphoma, and gastric carcinoma 2−7 . Other studies have also suggested an association between H. pylori infection and other conditions such as ischemic heart disease and chronic urticaria 8,9 …”
mentioning
confidence: 99%
“…Most studies that have used the 13 C UBT in children have been published since 1997. These studies have evaluated the prevalence of H pylori infection in different pediatric populations (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and spontaneous clearance of infection in preschoolers (7,15,16), as well as the success of eradication after treatment (4,(17)(18)(19).…”
mentioning
confidence: 99%